Synthesis and use of bimetals and bimetal oxides in contaminants removal from water: a review. Issue 104 (11th November 2015) - Fu, Fenglian; Cheng, Zihang; Lu, Jianwei
<x xml:space="preserve">Abstract</x> This paper gives an overview of the recent advances of the synthesis methods of bimetals and bimetal oxides and applying them in contaminant removal from water.